2021
DOI: 10.3390/agronomy11010177
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Drought Tolerance and Striga hermonthica Resistance in Maize Using Newly Derived Inbred Lines from the Wild Maize Relative, Zea diploperennis

Abstract: Recurrent drought and Striga hermonthica (Del.) Benth parasitism constrains maize production in sub-Saharan Africa (SSA). Transfer of resistance genes from wild relatives can improve resistance to drought and Striga in tropical maize. The objectives of this study were to (i) determine the combining ability of 12 extra-early yellow maize inbreds derived from Zea diploperennis and tropical maize germplasm; (ii) classify the inbreds into heterotic groups using heterotic grouping based on the general combining abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Given that these genotypes have good general combining ability, female parental genotypes with a great potential to transmit on desirable traits to their cross progeny could be used as a substantial material to improve the qualities of interest [ 11 , 42 ]. The significant GCA effects reported in the current investigation were consistent with those found in prior studies [ 31 , 60 62 ]. Positive and significant GCA effects observed in the current study for female parental genotypes and testers are significantly vital.…”
Section: Discussionsupporting
confidence: 92%
“…Given that these genotypes have good general combining ability, female parental genotypes with a great potential to transmit on desirable traits to their cross progeny could be used as a substantial material to improve the qualities of interest [ 11 , 42 ]. The significant GCA effects reported in the current investigation were consistent with those found in prior studies [ 31 , 60 62 ]. Positive and significant GCA effects observed in the current study for female parental genotypes and testers are significantly vital.…”
Section: Discussionsupporting
confidence: 92%
“…Also, cross (L 3 × T 3 ) showed good SCA effect for ears dry weight/ plant (under stress irrigation regime). In this concern, Sakr and Ghazy (2010), Abdel-Aty et al (2013), Hatab (2014), Ghazy (2016), Habeba (2019) and Shaibu et al (2021) found highly significant positive SCA effects in maize × teosinte crosses in some growth characters and forage productivity.…”
Section: Specific Combining Ability: (Sca)mentioning
confidence: 81%
“…This means that those genotypes could be used as donors in program to improve the growth characters and forage productivity of maize and teosinte under any tested irrigation regimes. Rady (2007), Sakr and Ghazy (2010), Meseka et al, (2011), Abd El-Zaher (2016) and Shaibu et al (2021) they found positive GCA in some maize and teosinte genotypes in some growth characters and forage productivity.…”
Section: General Combining Ability: (Gca)mentioning
confidence: 96%
“…Host plant resistance remain the most sustainable, economically, and eco-friendly method to control the parasitic weeds. Striga-resistance is a polygenic trait that requires combining whole-genome information (Badu-Apraku et al, 2020a;Shaibu et al, 2021). Genotyping and phenotyping are therefore critical to correlate the resistance-associated traits with particular gene loci.…”
Section: Genetic Basis For Host Plant Resistance and Defence Mechanismsmentioning
confidence: 99%